BV-FAPESP: um modelo de biblioteca virtual para democratização do acesso à informação pública no Brasil - Morais, Thais Fernandes de; Pereira, Fabiana Andrade; Krzyzanowski, Rosaly Fávero; Imperatriz, Inês Maria M.; Hashimoto, Paula Harumi K. (Cadernos BAD, 2014)
BV-FAPESP: um modelo de biblioteca virtual para democratização do acesso à informação pública no Brasil